Why Was Andrew Surprised? - Youd, Pauline (Scandinavia, 2010)
Bedtime Bible Stories with little wondering questions for little people. The answer come alive in these simple retellings of twelve favourite Bible stories, including the stories of David, Pharaoh, Deborah, Gideon, Nehemiah, Mary Magdalene, The Good Shepherd and Andrew.
Keywords: Juvenile literature- Non-Fiction